Perbandingan Pemanfaatan Media Buku Teks dengan Media Digital untuk Meningkatkan Pemahaman Siswa pada Materi Drama - Putri Mahrizki; Muhammad Darwis; Ezmar (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
"A Comparison of the Use of Textbooks and Digital Media to Improve Understanding of Drama Material." This research was conducted at SMP Negeri 15 Takengon with eighth-grade students. The aim of this study is to identify the comparison between the use of textbooks and digital media in teaching drama material, as well as to determine the effectiveness of each media type. This research employed a quantitative method with an experimental approach. The research design used was a pretest-posttest experimental design with two groups: experimental group 1 and experimental group 2. Based on data description and t-test analysis, both classes showed significant differences, indicating a variance in the effectiveness of using textbooks versus digital media for drama material. The results showed that digital media was more effective than textbooks in enhancing students’ understanding of drama. Through questionnaires and written tests, it was revealed that students found digital media to be more effective than textbooks in improving their comprehension of drama material.